On Stability of Linear Delay Differential Equations under Perron's Condition - J. Diblík; A. Zafer (Abstract and Applied Analysis)
The stability of the zero solution of a system of first-order linear functional differential equations with nonconstant delay is considered. Sufficient conditions for stability, uniform stability, asymptotic stability, and uniform asymptotic stability are established.